2015
DOI: 10.1039/c5cp03831f
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced water splitting via benzoquinone and semiquinone sensitisation

Abstract: The splitting of water into H· and OH· radicals by sensitisation of a redox-active chromophore with sunlight may eventually become a viable way of producing unlimited, clean and sustainable energy. In this work, we explore the possibility of photo-oxidation of water via sensitisation of benzoquinone with ultraviolet (UV) light in the hydrogen-bonded complex of benzoquinone with a single water molecule. Using state-of-the-art quantum chemical calculations, the mechanisms of electron/proton transfer reactions be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 52 publications
(101 reference statements)
7
30
0
Order By: Relevance
“…Such species typicallyf orm by disproportionation reactions of SQ dianions in solution ( Figure 7b). [58,73,74] The parameters of the ED EPR spectra correspond to the g tensors with values that are in accordance with those typically observed for SQ radicals, confirming the identification of the paramagnetic species. [59,67,71,75] Furthermore, the spin state assignment of the speciesc an be evidenced by comparing the nutation frequency (n nut )o ft he EPR signal with that of ar eference system with known spin state.…”
Section: Electroswitchable Molecular Gripperssupporting
confidence: 85%
See 1 more Smart Citation
“…Such species typicallyf orm by disproportionation reactions of SQ dianions in solution ( Figure 7b). [58,73,74] The parameters of the ED EPR spectra correspond to the g tensors with values that are in accordance with those typically observed for SQ radicals, confirming the identification of the paramagnetic species. [59,67,71,75] Furthermore, the spin state assignment of the speciesc an be evidenced by comparing the nutation frequency (n nut )o ft he EPR signal with that of ar eference system with known spin state.…”
Section: Electroswitchable Molecular Gripperssupporting
confidence: 85%
“…The other signal of the minor species becomes apparent close to the center of the spectrum (purple arrow at B 0 =348.5 mT in Figure a) and can be ascribed to the monoanion in the doublet spin state D ( S =1/2 ). Such species typically form by disproportionation reactions of SQ dianions in solution (Figure b) . The parameters of the ED EPR spectra correspond to the g tensors with values that are in accordance with those typically observed for SQ radicals, confirming the identification of the paramagnetic species .…”
Section: Electroswitchable Molecular Gripperssupporting
confidence: 79%
“…The second quasi‐reversible reduction wave was attributed to formation of the quinone‐dianion Q 2− (Figure a; for details see Section S4, Supporting Information) . UV/Vis spectroelectrochemistry upon electrochemical reduction in the domain of the first reduction wave revealed absorption in the range between 450 and 550 nm, which was an indication of the SQ state formation (Figure b) . This spectroscopic signature was also identified by UV/Vis transient absorption spectroscopy upon photochemical reduction (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The reversibility of this process was assessed by monitoring the evolution of the SQ À * wall absorption in the UV-Vis spectrum (Figure 6,b). [16,17,30,31] Periodic changes of the absorption at 456 nm, 340 nm, and 247 nm over several reduction-oxidation cycles confirmed that the redox interconversion features remarkable reversibility, particularly in the case of triptycene-quinone 2. Naphthoquinone-derived cavitand 1 displays two stepwise changes of the absorptions at 340 nm and 247 nm (for details, see Section S6 in the Supporting information), which likely indicates that the conformational change takes place on a slower time scale compared to the redox interconversion as a result of the effect of the nature of the redox-active quinone walls on the stabilization of the closed form.…”
Section: Resultsmentioning
confidence: 84%
“…UV-Vis-NIR spectra correlating to the first reduction wave of 1 and 2 confirmed formation of the SQ state through appearance of a visible absorption between 400 and 500 nm that can be attributed to the SOMO-LUMO transitions ( Figure 5). [16,17,30,31] Furthermore, inspection of the spectroscopic changes in the quinoxaline (Qx) absorption domain revealed a hypo-hypsochromic shift of the absorption between 300 and 350 nm for both cavitands 1 and 2 ( Figures 5,a and 5,b). This suggests that a conformational change to (111) showing binding energies in the spectral range of S 2p core-level peaks, which evidences the interaction of the thioether groups with the Au surface.…”
Section: Resultsmentioning
confidence: 99%